The illustrated dictionary of electronics - Gibilisco, Stan (McGraw-Hill, 1997)
More than 27,500 definitions - plus over 1,000 clear and functional illustrations - make the Seventh Edition the ultimate reference for technicians, hobbyists, and students. Many new terms and illustrations from robotics, artificial intelligence, and personal computing as they relate to electronics are included. Definitions spelled out in plain English with minimal technical jargon make the Dictionary accessible to beginning, intermediate, and advanced electronics professionals. You'll find coverage of the latest terminology in lasers, television, radio, IC technology, digital and analog electronics, audio and video, power supplies, fiber optic communications and more! Existing definitions have been updated, obsolete material has been deleted, and all entries have been reviewed by an editorial review board to assure their accuracy.